State of Charge Estimation for Lithium-Ion Battery Using Recurrent NARX Neural Network Model Based Lighting Search Algorithm - Lipu M.S.H.; Hannan M.A.; Hussain A.; Saad M.H.M.; Ayob A.; Blaabjerg F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Backpropagation; Charging (batteries); Ions; Learning algorithms; Lighting; Lithium-ion batteries; Particle swarm optimization (PSO); Radial basis function networks; Back-propagation neural networks; Electrochemical reactions; NARX neural network; Non-linear autoregressive with exogenous; Radial basis function neural networks; Search Algorithms; State of charge; State-of-charge estimation; Battery management systems